The mammalian target of rapamycin contributes to synovial fibroblast pathogenicity in rheumatoid arthritis - Barker, Brianne E.; Hanlon, Megan M.; Marzaioli, Viviana; Smith, Conor M.; Cunningham, Clare C.; Fletcher, Jean M.; Veale, Douglas J.; Fearon, Ursula; Canavan, Mary (Frontiers in Medicine, 2023)
The mammalian target of Rapamycin (mTOR) is a metabolic master regulator of both innate and adaptive immunity; however, its exact role in stromal cell biology is unknown. In this study we explored the role of the mTOR pathway on Rheumatoid Arthritis synovial fibroblast (RASF) metabolism and activation and determined if crosstalk with the Hippo-YAP pathway mediates their effects. Methods: Primary RA synovial fibroblasts (RASF) were cultured with TNFα alone or in combination with the mTOR inhibitor Rapamycin or YAP inhibitor Verteporfin. Chemokine production, matrix metalloproteinase (MMP) production, and adhesion marker expression were quantified by RTPCR, ELISA, and/or Flow Cytometry. Invasion assays were performed using Transwell invasion chambers, while wound repair assays were used to assess RASF migration. Cellular bioenergetics was assessed using the Seahorse XFe96 Analyser. Key metabolic genes (GLUT-1, HK2, G6PD) were measured using real-time PCR. Reanalysis of RNA-Seq analysis was performed on RA (n=151) and healthy control (HC) (n=28) synovial tissue biopsies to detect differential gene and pathway expression. The expression of YAP was measured by Western Blot. Results: Transcriptomic analysis of healthy donor and RA synovial tissue revealed dysregulated expression of several key components of the mTOR pathway in RA. Moreover, the expression of phospho-ribosomal protein S6 (pS6), the major downstream target of mTOR is specifically increased in RA synovial fibroblasts compared to healthy tissue. In the presence of TNFα, RASF display heightened phosphorylation of S6 and are responsive to mTOR inhibition via Rapamycin. Rapamycin alters RASF cellular bioenergetics by inhibiting glycolysis and the expression of rate limiting glycolytic enzymes. Furthermore, we demonstrate a key role for mTOR signaling in mediating RASF migratory and invasive mechanisms, which are significantly abrogated in the presence of Rapamycin. Finally, we report a significant upregulation in several genes involved in the Hippo-YAP pathway in RA synovial tissue, which are predicted to converge with the mTOR pathway. We demonstrate crosstalk between the mTOR/YAP pathways in mediating RASF invasive mechanism whereby Rapamycin significantly abrogates YAP expression and YAP inhibition significantly inhibits RASF invasiveness. Conclusions: mTOR drives pathogenic mechanisms in RASF an effect which is in part mediated via crosstalk with the Hippo-YAP pathway.